A meta-analysis of the impact of human leukocyte antigen-G on the outcomes of IVF/ICSI. Issue 6 (June 2017) - Niu, Ziru; Wang, Liangyi; Pang, Ronald T.K.; Guo, Yifan; Yeung, William S.B.; Yao, Yuanqing
Abstract: This analysis was performed to determine whether the presence of soluble human leukocyte antigen-G (sHLA-G) in embryo culture medium is predictive of clinical outcomes in IVF treatment. The outcomes of implantation, clinical pregnancy, multiple pregnancy and miscarriage, between groups with and without sHLA-G in embryo culture media, were analysed. Fifteen studies with a total of 6170 cases were included. Ten of them were prospective studies while five were retrospective studies. Embryo culture media with sHLA-G were associated with significantly higher implantation rate and clinical pregnancy rate when compared with those without; the odd ratios (ORs) were 2.66 [95% confidence interval (CI): 1.75–4.06, P < 0.00001], 3.79 (95% CI: 2.69–5.33, P < 0.00001), respectively. There was no significant difference in the rate of multiple pregnancy (OR: 1.87, 95% CI: 0.55–6.31) and miscarriage (OR: 0.77, 95% CI: 0.52–1.16). The results suggested that the presence of sHLA-G in the embryo culture medium favoured higher implantation rate and pregnancy rate. However, the conclusion needs to be consolidated by further clinical studies using a more precise method of determination of sHLA-G and research on the physiological and molecular mechanisms of the beneficial effect of sHLA-G on early embryo development and implantation.